KERAGAAN TANAMAN KENTANG (Solanum tuberosum L.) VARIETAS GRANOLA AKIBAT PERLAKUAN PUPUK ANORGANIK - Yudi Yusdian, Joko Santoso dan Imar Dasimah (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2022)
Potato plants are one of the supporting commodities for the food diversification program because they have a high protein content. In addition, the potato plant is a strategic commodity in the supply of foodstuffs to support food. The need for potatoes is increasing, due to population growth and increasing public awareness of nutrition and the widespread use of potato production for various foodstuffs, foodstuffs. The aim of this research is to effect of NPK dosage fertilizer (15:15:15) on growth and yield. potato (Solanum tuberosum L.) Granola variety and to get the NPK dosege fertilizer (15:15:15) which is the NPK dosege fertilizer (15:15: 15) which is obtained and the yield of potato (Solanum tuberosum L.) granola variety. The experiment was conducted in Sukamenak Village RT 007 RW 018 Pangalengan Village, Pangalengan District, Bandung Regency, West Java Province. With an altitude of 1,400 meters above sea level (m asl). Rainfall 2,844 mm/year including type C2 rainfall based on Oldeman's classification (1979). Andisol soil type with a pH of 6.8. The experiment was carried from September until December 2021. The research method used was a randomized block design (RBD) consisting of six treatments and four replications. NPK fertilizer dosage (15:15:15) treatments are as follows: A (0 kg/ha), B (800 kg/ha), C (900 kg/ha), D (1000 kg/ha), E (1100 kg/ha) and F (1200 kg/ha). The results showed that giving a dosege 800 kg/ha of NPK fertilizer (15:15:15) had a better effect on plant height, number of leaves and tuber weight per plot.